Employee Performance: Application Of Ethics And Motivation And Discipline As Intervening - Hefriansyah Hefriansyah (International Journal Reglement & Society (IJRS), 2023)
This research is a causal approach. The population in this study is all employees of PT Perkebunan Nusantara IV (Persero). The sample in this study used the slovin formula puller so that a total of 80 employees of PT Perkebunan Nusantara IV (Persero). Data collection techniques in this study used documentation, observation, and questionnaire techniques. Data analysis techniques in this study used a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study uses the PLS (Partial Least Square) software program. The results of this study prove that self-efficacy, work motivation and work discipline directly affect employee performance, self-efficacy and work motivation affect work discipline. Indirectly, self-efficacy and work motivation affect employee performance in the medium of work discipline.